Clinical and Histopathological Profile of Breast Cancer Based on HER2 Stratification ASCO/CAP 2018: Analysis of HER2-Positive, Negative, Low, and Ultralow - Novasari; Citra Dewi; Sandria; Nora Ramkita (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. The emerging classification of HER2-low and HER2-ultralow breast cancer subtypes has important treatment implications, especially after the introduction of trastuzumab deruxtecan, which is effective in tumors exhibiting low levels of HER2 expression. However, data from Indonesia are still limited. This study aimed to characterize the clinicopathological features of Invasive Breast Cancer (IBC) according to the ASCO/CAP 2018 HER2 classification and to determine the proportion of HER2-negative patients who can be further categorized as HER2-low or HER2-ultralow. Methods. This retrospective descriptive-analytical study involved 50 patients diagnosed with IBC who underwent HER2 immunohistochemical evaluation at Mohammad Hoesin General Hospital, Palembang, in February 2023. The variables analyzed were age, ER/PR status, Ki-67 index, tumor-infiltrating lymphocytes (TILs), lymphovascular invasion (LVI), histological grade, and tumor subtype. Results. Of the 50 patients, 16 (32%) were categorized as HER2-positive and 34 (68%) were categorized as HER2-negative. Among the HER2-negative group, 10 patients (35.7%) were HER2-low and 5 patients (17.8%) were HER2-ultralow. The majority of patients were aged 40 years or older and ER-positive. A high Ki-67 index was observed in 84% of cases. Most tumors were grade II–III and of the NST subtype. No significant differences were observed between the HER2-low and HER2-ultralow groups (p>0.05). Conclusion. A considerable proportion of HER2-negative IBCs are categorized as HER2-low or HER2-ultralow. These findings highlight the importance of accurate HER2 assessment to identify patients who may benefit from antibody–drug conjugate therapy and to advance precision medicine in breast cancer management in Indonesia.